Commutation Algorithm for Three-Phase Unbalanced Load Regulation in Distribution Network - Yongxia LI; Yulei GONG; Xiuxiao GUO; Yanyan ZHAO (Zhongguo dianli)
Automatic phase commutation system is widely used to deal with the load imbalance problem in low voltage distribution network. It consists of an intelligent commutation terminal and a number of phase commutation switches. In the commutation switch, the compound switch of paralleled magnetic latching relay and bidirectional thyristor is selected as commutation switch actuator, in which the thyristor is cut off by zero switching at the moment of commutation, and the magnetic latching relay is switched on without large current. The hardware devices are generally used to detect the zero crossing point on the line voltage. As high frequency harmonic waves exist on the line voltage, the zero crossing point is hard to be detected accurately, and dedicated phase trigging can not be implemented using this method. Therefore, the software method is used to calculate the line voltage phase, and a reliable commutation algorithm is adopted to realize the regulation of three-phase imbalance, which effectively prevents the impact impulse to load and power grid, consequently improving the reliability in triggering thyristor. Experimental results show that the proposed algorithm is feasible in solving three-phase unbalanced loads and improving power supply quality.